Do Changes in Oral Microbiota Correlate With Plasma Nitrite Response? A Systematic Review - Zhurakivska, Khrystyna; Troiano, Giuseppe; Caponio, Vito Carlo Alberto; Dioguardi, Mario; Laino, Luigi; Maffione, Angela Bruna; Lo Muzio, Lorenzo (Frontiers in Physiology, 2019)
Background: Nitric Oxide (NO) has a role in immunitary defence, regulation of mucosal blood flow and mucus production, regulation of smooth muscle contraction, cerebral blood flow, glucose regulation and mitochondrial function. NO can be synthetized endogenously through the L-arginine-NO pathway or it can be absorbed by the human intestine through the dietary intake. Most of the ingested NO is in the form of nitrate (NO3-). NO3 - is a substrate of oral and intestinal microbiota and, at the end of the catabolic pathway, NO is released. Using antibacterial mouthwashes leads to an alteration of salivary NO3- metabolism, however, with unclear consequences on the circulating NO levels. The aim of this study is to perform a systematic review in order to elucidate if the alterations of oral microbiota lead to modifications in plasma NO content.Methods: Electronic databases were screened, using the following terms: (“oral bacteria” and (nitrate OR nitrite OR nitric)). Clinical studies reporting NO3- and NO2- measurements in blood and their correlation to oral microbiota variations were included. We focused on the correlation between the changes in oral microbiota and plasma concentrations of nitrites (primary outcome). Subsequently, we investigated if modifications in oral microbiota could lead to changes in blood pressure and salivary NO2- concentration (secondary outcome).Results: six studies, for a total of 82 participants were included in this review. In four studies, the use of mouthwash correlated to a reduction of plasma nitrite concentration (p<0.05);,Two studies did not find any difference in plasma nitrate or nitrite concentration. In five studies, a correlation between blood pressure (BP) changes and antibacterial mouthwashing emerged. Anyway, only three studies suggested a significant increase of systolic BP following mouthwashing compared with controls. Conclusions: Although, the role of oral bacteria has been unequivocally demonstrated in the regulation of salivary NO3- metabolism, their influence on plasma concentration of NO species remains ambiguous. Further studies with larger sample size are required in order to demonstrate if an alteration in oral microbiota composition may influence the blood content of NO3-/NO2-/NO and all the linked biological processes.